Uso de blog como recurso didáctico en el curso de integración a las tecnologías de la información y comunicaciones de la carrera técnica de computación e informática del I.E.S.T. AMAZÓNICO en el semestre 2013-I - Águila Gonzales, Javier Del (2013)
The following research is based on the influence of BLOG used as a teaching resource to improve the academic performance of students in the course of Integration of information Technology and communication. This research takes as shown to the students of first grade of “Technical course of computing and information” in “AMAZONICO” High Education Institute of Technology. The research was conducted with two groups, experimental and control groups in both groups a Pre and Post Test was applied, which was referred to conduct a survey about the course, later with the experimental group, a new teaching model, which consisted of implementing a blog for students to have a new tool in which to clear their doubts and concerns about the subject in class was implemented, achieving strengthen and increase awareness and participation in the formulation of questions by students, also homogeneous growth in the level of academic achievement for all students in the group, in the other hand the Control group with traditional teaching or classroom assessment by teacher only we notice the lack of growth, getting to note the significant influence of BLOG in improving the academic performance of students